Neural Correlates of Facial Expression Recognition in Earthquake Witnesses - Pistoia, Francesca; Conson, Massimiliano; Quarantelli, Mario; Panebianco, Luca; Carolei, Antonio; Curcio, Giuseppe; Sacco, Simona; Saporito, Gennaro; Di Cesare, Ernesto; Barile, Antonio; Masciocchi, Carlo; Splendiani, Alessandra (Frontiers in Neuroscience, 2019)
Major adverse events, like an earthquake, trigger different kinds of emotional dysfunctions or psychiatric disorders in the exposed subjects. Recent literature has also shown that exposure to natural disasters can increase threat detection. In particular, we previously detected a selective increase in the ability to read emotional facial expressions in L’Aquila earthquake witnesses, suggesting hypervigilance to stimuli signaling a threat. In the light of previous neuroimaging data showing that trauma exposure is related to derangement of resting-state brain activity, in the present study we investigated the neurofunctional changes related to the recognition of emotional faces in L’Aquila earthquake witnesses. Specifically, we tested the relationships between accuracy in recognizing facial expressions and activity of the visual network (VN) and of the default-mode network (DMN). Resting-state functional connectivity with the main hub of the VN (primary, ventral, right-dorsal and left-dorsal visual cortices) and DMN (posterior cingulate/precuneus, medial prefrontal, right and left inferior parietal cortices) was investigated through a seed-based fMRI analysis in both earthquake-exposed subjects and non-exposed persons who did not live in an earthquake-affected area. The results showed that, in earthquake-exposed subjects, there is a significant reduction in the correlation between accuracy in recognizing facial expressions and the functional connectivity of the dorsal seed of the VN with the right inferior occipito-temporal cortex and the left lateral temporal cortex, and of two parietal seeds of DMN, i.e., lower parietal and medial prefrontal cortex, with the precuneus bilaterally. These findings suggest that a functional modification of brain systems involved in detecting and interpreting emotional faces may represent the neurophysiological basis of the specific “emotional expertise” observed in the earthquake witnesses.